HTML5 Canvas : native interactivity and animation for the Web - Fulton, Steve; Fulton, Jeff. (Sebastopol, CA : O'Reilly, 2011)
"No matter what platform or tools use, the HTML5 revolution will soon change the way you build web applications, if it hasn't already...Whether you currently use Flash, Silverlight , or just HTML and JavaScript, you'll quickly pick up the basics. Practical examples show you how to create various games and entertainment applications with Canvas as you learn...Create and modify 2D drawings, text, and bitmap images ; Incorporate and manipulate video, and add audio ; Build a basic framework for creating a variety of games on Canvas ; Use bitmaps and tile sheets to develop animated game graphics ; Go mobile: port Canvas applications to iPhone with PhoneGap ; Explore ways to use Canvas for 3D and multiplayer game applications..."--P. [4] of cover.
Introduction to HTML5 Canvas -- Drawing on the Canvas -- The HTML5 Canvas text API -- Images on the Canvas -- Math, physics, and animation -- Mixing HTML5 video and Canvas -- Working with audio -- Canvas game essentials -- Combining bitmaps and sound -- Mobilizing games with PhoneGap -- Further explanations.
Includes index.
Keywords: Canvas (Computer file); Application software -- Design; Cascading style sheets; Computer drawing; Computer games -- Computer software; Computer graphics; HTML (Document markup language); HTML (Document markup language); HTML 5.0.; TML 5.0.; Web site development; Web sites -- Design